CO2 methanation on the effect of metal supported catalyst / Syamil Azim Saharuddin and Siti Aminah Md Ali - Saharuddin, Syamil Azim; Md Ali, Siti Aminah (2020)
Rapid population growth has contributed significantly to the increasing demand for natural resources consumption. An initiative that can be made in conserving the natural resources is by CO2 methanation that converts CO2 to the methane gas. Catalyst plays a significant role in promoting the CO2 methanation in achieving high methane selectivity. The catalytic activity, selectivity, stability and cost must take consideration towards the selection of suitable methanation catalyst in certain reaction conditions. The methanation catalysts that had been reviewed based on their catalytic activity are noble metal such as Rhodium and Ruthenium, Nickel and Cobalt catalyst. The noble metal catalysts such as Ru and Rh are the most active metal in group VIII which possess higher methane selectivity produced at low temperature due to its high resistance for the carbon dioxide, CO2 oxidized to the atmospheres. Supported Rh/ - Al2O3 catalyst increase the CO2 adsorption and CO2 dissociation compared to unsupported Rh catalyst in hydrogenation of CO2 to methane process. The increase of Rh loading from 1 wt% to 10 wt% resulted higher methane selectivity in the process. The co-precipitated of zirconia dioxide support resulted the greater CO conversion in 20 wt% Ni/ZrO2 catalyst compared to solgel method. The different types of support were used in Ni catalyst such as CeO2, ZrO2, TiO2, SiO2, and Al2O3 to observed the most suitable support in low temperature process. The strong interaction between Ni and Ce support possess the highest catalytic activity based on the percentage of methane yield. The effect of support and metal loading for cobalt catalyst shows that 230 m2/g of support Co/CeO2 and increasing from 5 wt% to 10 wt % of Co/CNT catalyst produced higher CO conversion in the CO2 methanation process. The addition of support and effect of metal loading has influenced the catalytic performance of the catalyst in the reaction. Therefore, the supported Ni with Cerium (IV) oxide, Ni-CeO2 is the best combination and economical methanation catalyst used in large industrial scale based on their results on the catalytic activity from the research studies.